2004
DOI: 10.1002/jgm.629
|View full text |Cite
|
Sign up to set email alerts
|

Purine nucleoside phosphorylase and fludarabine phosphate gene‐directed enzyme prodrug therapy suppresses primary tumour growth and pseudo‐metastases in a mouse model of prostate cancer

Abstract: Gene-directed enzyme prodrug therapy based on the E. coli purine nucleoside phosphorylase (PNP) gene produces efficient tumour cell killing. PNP converts adenosine analogs into toxic metabolites that diffuse across cell membranes to kill neighbouring untransduced cells (PNP-GDEPT). Interference with DNA, RNA and protein synthesis kills dividing and non-dividing cells, an important consideration for slow-growing prostate tumours. This study examined the impact of administering PNP-GDEPT into orthotopically grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Mice given PNP-GDEPT showed a significant reduction both in prostate volume and in lung colony counts. Apoptosis was increased two-fold in treated prostates compared to controls (Martiniello-Wilks et al, 2004). Thus preclinical studies using animal models have demonstrated that PNP anticancer gene therapy is a promising approach for the treatment of solid tumors.…”
Section: Purine Nucleoside Phosphorylase/fludarabine Approachmentioning
confidence: 98%
“…Mice given PNP-GDEPT showed a significant reduction both in prostate volume and in lung colony counts. Apoptosis was increased two-fold in treated prostates compared to controls (Martiniello-Wilks et al, 2004). Thus preclinical studies using animal models have demonstrated that PNP anticancer gene therapy is a promising approach for the treatment of solid tumors.…”
Section: Purine Nucleoside Phosphorylase/fludarabine Approachmentioning
confidence: 98%
“…RM1 cells express androgen receptors and yet display androgen independence (the most aggressive CRPC phenotype encountered in humans), forming aggressive tumors. The RM1 model has been successfully used in preclinical studies to evaluate different anticancer therapies against local and metastatic PCs (9,11,18,20,24). (ii) Human PC-3 cells that exhibit several characteristics of late-stage CRPC and provide a clinically relevant model to assess antitumor responses of various therapies (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, PNP-GDEPT efficacy against late-stage PC has been previously shown in our laboratory in xenogeneic and syngeneic mouse models of local and metastatic CRPC (human PC-3 and murine RM1; refs. [9][10][11], and significantly, PNP-GDEPT prolonged survival rate of mice with transgenic adenocarcinoma of the prostate (TRAMP; ref. 12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Both prodrug-activating systems induce apoptosis in Transduction of PNP gene followed by treatment with nucleoside analogues has been studied in vivo on bladder tumors, pancreatic adenocarcinomas, gliomas, ovarian or prostate tumors and showed different levels of growth inhibition. 40,44,[49][50][51][52][53][54][55][56] To increase the effect obtained with this gene-therapy approach by using new genes and new drugs, a study based on crystallographic and computer modeling of E. coli PNP, was performed. The mutated protein (M64V) had a more than 100-fold increased enzymatic efficiency (kcat/Km) toward the nontoxic 9-(6-deoxy-a-L-talofuranosyl)-6-methylpurine as compared to the wt protein.…”
Section: Gene Therapy and Nucleoside Analogues C Hébrard Et Almentioning
confidence: 99%